2022
DOI: 10.1155/2022/6012518
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Experimental Investigations of Tribological and Corrosion Performance of AZ61 Magnesium Alloy Hybrid Composites

Abstract: Magnesium alloy is the light weight material compared to aluminium alloy, and it possesses high strength; these alloys are used to manufacturing of vehicle parts. Magnesium alloy has extreme mechanical and thermal properties, and it is applied to aerospace applications. This study planned to improve the tribological and corrosion resistance of AZ61 magnesium alloy with reinforcement of boron carbide (B4C) and zirconium dioxide (ZrO2). Magnesium alloy hybrid composites are fabricated through stir casting proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Application areas of magnesium metal matrix composites are piston, brake components, and steering shafts are some of Magnesium matrix composite. 6 In fabrication of magnesium matrix composite, processes such as; stir casting, powder metallurgy, friction stir processing, and squeeze infiltration technique have been implemented and results showed that the addition of MoS 2 and TiC improves the wear property of the matrix and good wettability property were achieved. 7 Magnesium matrix composite is alternatively preferable than aluminum matrix composite due to it has less density and high strength to weight ratio in addition to its wettability property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application areas of magnesium metal matrix composites are piston, brake components, and steering shafts are some of Magnesium matrix composite. 6 In fabrication of magnesium matrix composite, processes such as; stir casting, powder metallurgy, friction stir processing, and squeeze infiltration technique have been implemented and results showed that the addition of MoS 2 and TiC improves the wear property of the matrix and good wettability property were achieved. 7 Magnesium matrix composite is alternatively preferable than aluminum matrix composite due to it has less density and high strength to weight ratio in addition to its wettability property.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of ZrO 2 in the magnesium alloy of AZ61 metal matrix enhances the wear resisting property of a composite. 6 Likewise, researchers studied the effects of ZrO 2 in AZ31 magnesium alloy and results depicts that there was an improvement in yield strength of a base material from 137 to 217 MPa of ZrO 2 reinforced magnesium alloy AZ31. 13 This shows that, the influence of ZrO 2 in magnesium alloy matrix is not only wear property enhancement but also yield strength.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the waste of non‐biodegradable fibers is discarded into landfilling, resulting in giant environmental pollution (De Paiva et al., 2019). These natural fibers are chosen as alternatives and they contain low amounts of CO 2 , enhanced flexural strength, less weight, high tensile strength, low greenhouse emission, good thermal insulation, and successful acoustic effect (Aslan et al., 2018; Kannan et al., 2022). The various natural fibers are ramie, jute, cotton, banana, sisal, kenaf, coir, pineapple, and Bagasse, utilized as reinforcement for epoxy composites and attain specific properties like good tensile strength, impact toughness, good tribological characteristics, enhanced thermal insulation properties and less gas emission (Nguyen et al., 2019; Sumesh et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The waste recycled metal scrap reinforced aluminum alloy composite quality was experimentally evaluated by ASTM test standards (Overcash et al., 2017; Ramesh Kannan et al., 2022). Moreover, the developed composite characteristics like weight, mechanical strength, wear properties, and other properties were higher than the value of conventional cast alloy (Amaechi et al., 2020; Kahveci & Unal, 2000).…”
Section: Introductionmentioning
confidence: 99%